2020
DOI: 10.1186/s12879-020-05081-9
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus positive status disclosure to a sexual partner and its determinant factors in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Disclosure of Human Immunodeficiency Virus positive status significantly reduced the transmission of HIV; yet, it remains a challenge for many HIV patients. Disclosure serves plays a crucial role to raise awareness and to reduce risky behaviors. Hence, this study aimed to determine the pooled prevalence and effect sizes of determinant factors of HIV positive status disclosure through a systematic review and meta-analysis of the results of the existing primary studies in Ethiopia. Method: This syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…One ( 31 ) reported 76.03% of pooled disclosure rate (18 studies, 8,009 participants), while the other ( 32 ) reported 73% of disclosure rate (12 studies, 4,528 participants). Two other reviews ( 33 , 34 ) reported 74.63% (22 studies, 8,873 participants) and 75.95% (18 studies, 7,084 participants) disclosure proportions, respectively. However, there is still a lack of knowledge about the special characteristics of HIV disclosure to sexual partners ( 31 34 ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…One ( 31 ) reported 76.03% of pooled disclosure rate (18 studies, 8,009 participants), while the other ( 32 ) reported 73% of disclosure rate (12 studies, 4,528 participants). Two other reviews ( 33 , 34 ) reported 74.63% (22 studies, 8,873 participants) and 75.95% (18 studies, 7,084 participants) disclosure proportions, respectively. However, there is still a lack of knowledge about the special characteristics of HIV disclosure to sexual partners ( 31 34 ).…”
Section: Introductionmentioning
confidence: 97%
“…Two other reviews ( 33 , 34 ) reported 74.63% (22 studies, 8,873 participants) and 75.95% (18 studies, 7,084 participants) disclosure proportions, respectively. However, there is still a lack of knowledge about the special characteristics of HIV disclosure to sexual partners ( 31 34 ). The quality of the reviews was also low, resulting in high publication bias ( 32 , 34 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A systematic review by Yehualashet et al . [ 91 ] indicated that the pooled national estimate of HIV-positive status disclosure among adult PLHIVs was lower in Ethiopia than in developing countries. This study found that PLHIVs with non-disclosure status had threefold higher mortality hazards than those who disclosed their status.…”
Section: Discussionmentioning
confidence: 99%